2015
DOI: 10.4315/0362-028x.jfp-14-395
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Load and Zoonotic Agents in Beef Mortadella from Addis Ababa City Supermarkets

Abstract: Processing changes the meat ecosystem and, hence, has an impact on the microbiological load and quality of the product. Microbial contamination decreases shelf life and, if a pathogen is present, increases the risk of zoonoses in humans. The aim of this study was to assess the microbiological load, including zoonotic agents, in ready-to-eat beef mortadella from Ethiopian supermarkets. A total of 119 samples from 8 supermarkets in Addis Ababa City (Ethiopia) were examined for aerobic plate count, Enterobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…(2012) 2012 450 51 11.33 Central Ethiopia Culture and biochemical test - Milk Hilali et al. (2016) 2016 19 7 36.84 Northern Ethiopia Culture and biochemical test - Milk Hiko et al. (2015) 2015 119 35 29.41 Central Ethiopia Culture and biochemical test - Beef Hiko et al.…”
Section: Resultsmentioning
confidence: 99%
“…(2012) 2012 450 51 11.33 Central Ethiopia Culture and biochemical test - Milk Hilali et al. (2016) 2016 19 7 36.84 Northern Ethiopia Culture and biochemical test - Milk Hiko et al. (2015) 2015 119 35 29.41 Central Ethiopia Culture and biochemical test - Beef Hiko et al.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the prevalence of E. coli in the current study was higher than the reports of Messele et al [7] in Addis Ababa and Bishoftu towns (5.5%), Messele et al [12] in central Ethiopia (Sebeta, Burayu, and Holeta towns) (7.1%), Kumar and Prasad [69] in and around PLOS NEGLECTED TROPICAL DISEASES Pantnagar (India) (8.14%), Yakubu et al [70] in Sokoto Metropolis (Nigeria) (9.23%), Mengistu et al [71] in Eastern Ethiopia (12.41%), Ngaywa et al [72] in Kenya (13.8%), Mohammed et al [73] in Dire Dawa city (15.89%), Ababu et al [17] in Holeta District (19.0%), Hiwot et al [74] in Arsi and East Shewa Zones (19.8%), Bedasa et al [19] in Bishoftu town (20.0%), Sebsibe and Asfaw [75] in Jimma town (20.2%), Tadese et al [76] in Ambo town (23.4%), Abebe et al [77] in selected districts of Tigray (23.7%), Abayneh et al [78] in Jimma town (23.9%), Yohannes [79] in Mekelle town (25.0%), Haileselassie et al [80] in Mekelle city (27.3%), Hiko et al [81] in Addis Ababa (29.0%), Momtaz et al [82] in Iran (29.7%), Taye et al [83] in Haramaya University abattoir (30.97%), Disassa et al [8] in and around Asosa town (33.9%), Tadesse et al [53] in Mekelle town (36.63%), Thaker et al [84] in Anand Gujarat (India) (38.0%), Zerabruk et al [85] in Addis Ababa (43.75%), Sobeih et al [86] in Kafr El-Sheikh Governorate (Egypt) (44.44%), and Welde et al [87] in and around Modjo town (46.26%). The result obtained from the current bacteriological study revealed that the overall prevalence of E. coli O157:H7 was 6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…in chevon was higher than that reported in a study cited above (7.6%) [ 41 ]. The higher level of isolation rates observed could be a reflection of the contamination of carcasses with the animals’ intestinal contents during manual skinning, evisceration, washing and further processing in slaughterhouses or can be due to more frequent contact occurring between the hands of operators and their knives [ 44 ]. A recent meta-analysis revealed that the pooled prevalence of Campylobacter sp.…”
Section: Discussionmentioning
confidence: 99%